Antibacterial Nanoagents: Nonchemotherapic and Robust Dual‐Responsive Nanoagents with On‐Demand Bacterial Trapping, Ablation, and Release for Efficient Wound Disinfection (Adv. Funct. Mater. 21/2018). (May 2018) - Yang, Ye; Ma, Lang; Cheng, Chong; Deng, Yiyi; Huang, Jianbo; Fan, Xin; Nie, Chuanxiong; Zhao, Weifeng; Zhao, Changsheng
Abstract : A nonchemotherapeutic and robust dual‐responsive antibacterial nano‐agents to control the trapping, ablation and release of pathogenic bacteria is established and studied by Chong Cheng, Chuanxiong Nie, Changsheng Zhao, and co‐workers in article number1705708 . This novel and unique nanoagent can serve as localized heating source to enhance photothermal ablation of bacteria, which provides a new pathway for wound disinfection.